Development of a diagnostic system for detection of specific antibodies and antigens against Middle East respiratory syndrome coronavirus. (21st September 2018) - Lee, Kunse; Ko, Hae Li; Lee, Eun‐Young; Park, Hyo‐Jung; Kim, Young Seok; Kim, Yeon‐Sook; Cho, Nam‐Hyuk; Park, Man‐Seong; Lee, Sang‐Myeong; Kim, Jihye; Kim, Hun; Seong, Baik Lin; et al.
ABSTRACT: Middle East respiratory syndrome coronavirus (MERS‐CoV) is a single‐stranded RNA virus that causes severe respiratory disease in humans with a high fatality rate. Binding of the receptor binding domain (RBD) of the spike (S) glycoprotein to dipeptidyl peptidase 4 is the critical step in MERS‐CoV infection of a host cell. No vaccines or clinically applicable treatments are currently available for MERS‐CoV. Therefore, rapid diagnosis is important for improving patient outcomes through prompt treatment and protection against viral outbreaks. In this study, the aim was to establish two ELISA systems for detecting antigens and antibodies against MERS‐CoV. Using a recombinant full‐length S protein, an indirect ELISA was developed and found to detect MERS‐CoV‐specific antibodies in animal sera and sera of patient with MERS. Moreover, MAbs were induced with the recombinant S protein and RBD and used for sandwich ELISA to detect the MERS‐CoV S protein. Neither ELISA system exhibited significant intra‐assay or inter‐assay variation, indicating good reproducibility. Moreover, the inter‐day precision and sensitivity were adequate for use as a diagnostic kit. Thus, these ELISAs can be used clinically to diagnose MERS‐CoV.